(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the use of code-switching as a stylistic element in literary texts. The purpose of this research is to investigate how writers employ two or more languages in one text to expose the identities of their characters, generate national and cultural color, increase emotional and expressive effects, and fulfill pragmatic purposes. Linguistic analysis is also used to some examples of English and Uzbek literary works. According to the study, code-switching is not only a communicative phenomenon, but also an important instrument for the development of artistic style.